Temporal Aspects of the Social Cost of Greenhouse Gases - Disa Thureson (Örebro University School of Business, 2016)
The purpose of this study is to investigate the temporal aspects of the social cost of greenhouse gases (GHGs). I am particularly interested in the interaction between time of emissions, discounting, and type of GHG (where different GHGs have different atmospheric lifetimes). I show graphically how the social costs of GHGs depend on different parameter values and how the global damage potential for methane and sulfur hexafluoride evolves over time. I find that that the calculation period ultimately should be modeled to be consistent with the discount rate and that the "global-warming potential" concept is unsuitable for calculating of the social cost of GHGs other than carbon dioxide.
Keywords: Q54; 330; Cost benefit analysis; Discount rates; Emissions pricing; Global warming potential